Associations between the mediterranean diet and sleep in older adults: Results from the hellenic longitudinal investigation of aging and diet study. Issue 11 (5th September 2018) - Mamalaki, Eirini; Anastasiou, Costas A; Ntanasi, Eva; Tsapanou, Angeliki; Kosmidis, Mary H; Dardiotis, Efthimios; Hadjigeorgiou, Giorgos M; Sakka, Paraskevi; Scarmeas, Nikolaos; Yannakoulia, Mary
Abstract : Aim: Although there is some evidence of the relationships between sleep duration/quality and nutrient and/or food intake, the associations between sleep and dietary patterns have been poorly explored. The aim of the present study was to evaluate sleep duration and quality in relation to adherence to the Mediterranean diet (MeDi), and to investigate the sex‐ and age‐specific associations in a population‐representative cohort of older adults. Methods: Participants from the Hellenic Longitudinal Investigation of Aging and Diet were included. The sample consisted of 1639 adults aged ≥65 years. Sleep duration and quality were assessed through a self‐report questionnaire, whereas adherence to the MeDi was evaluated by an a priori score. Results: Sleep quality was positively associated with the MeDi in the unadjusted and the adjusted model (age, sex, depression, years of education, body mass index, level of physical activity and total energy intake were added as covariates). In contrast, sleep duration was not associated with MeDi adherence either in the unadjusted or the adjusted models. In relation to the age‐related associations, sleep quality was positively associated with MeDi adherence in those aged ≤75 years, and not in those aged >75 years. Associations between sleep and MeDi did not differ between men and women. Conclusions: The present results suggest that sleep quality is associated with MeDi adherence in older adults; there are also age‐specific associations between sleep quality and the MeDi. Although additional studies are required, improvements in diet quality should be considered in the context of sleep management interventions in older individuals.Geriatr Gerontol Int 2018; 18: 1543–1548 .